(3LhGH eSGFd GdeYde GdQLhi GdeQTO dcd VGd Zhis - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3SdGe Ydjc CeG HYO , abO HdZfG cJGHc , hagefG eVehfg heG PcQJ ef Efc Chd ef HGjY s
(3BNQgG (B:s
(3hEf cQg Pdc , de jVQ EdG faSg hGdSdGe , hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
Keywords: (3Gdabg GdESdGejs